Механізм управління ризиками підприємства на основі організаційно-економічних підходів у цифровому середовищі - Степаненко, Р. Д. (ХНУРЕ, 2025)
The study is devoted to the organizational and economic mechanism of risk management in the conditions of digitalization. It is determined that an effective risk management mechanism helps enterprises increase their resistance to negative influences and ensure stability in difficult conditions. The formation of an enterprise's strategy for risk management in the conditions of digitalization involves the establishment of basic rules that allow corporate management bodies to manage risks. High-quality risk management and planning significantly increase the likelihood of obtaining a positive financial result in the conditions of the impact on the enterprise of numerous risks associated with the digitalization of business.
Keywords: управління ризиками підприємства; організаційно-економічні підходи